The jPOST environment: an integrated proteomics data repository and database. Issue Volume 47:Issue D1(2019) (8th October 2018) - Moriya, Yuki; Kawano, Shin; Okuda, Shujiro; Watanabe, Yu; Matsumoto, Masaki; Takami, Tomoyo; Kobayashi, Daiki; Yamanouchi, Yoshinori; Araki, Norie; Yoshizawa, Akiyasu C; Tabata, Tsuyoshi; Iwasaki, Mio; et al.
Abstract: Rapid progress is being made in mass spectrometry (MS)-based proteomics, yielding an increasing number of larger datasets with higher quality and higher throughput. To integrate proteomics datasets generated from various projects and institutions, we launched a project named jPOST (Japan ProteOme STandard Repository/Database, https://jpostdb.org/ ) in 2015. Its proteomics data repository, jPOSTrepo, began operations in 2016 and has accepted more than 10 TB of MS-based proteomics datasets in the past two years. In addition, we have developed a new proteomics database named jPOSTdb in which the published raw datasets in jPOSTrepo are reanalyzed using standardized protocol. jPOSTdb provides viewers showing the frequency of detected post-translational modifications, the co-occurrence of phosphorylation sites on a peptide and peptide sharing among proteoforms. jPOSTdb also provides basic statistical analysis tools to compare proteomics datasets.